Multidrug resistance of Escherichia coli in cats and the level of understanding of cat owners on antimicrobial resistance - Wibisono, F.J.; Widiasih, D.A.; Hung Nguyen-Viet (A and V Publications, 2024)
Multidrug resistance poses a global health risk to humans, animals, and the environment. The impact of this issue is so great that it has gained international attention, ranging from the rising morbidity to the mortality rate of infectious diseases in humans and animals. Because of their peculiar eliminative behavior habit of burying their waste in the ground, cats may contribute to the spread of microorganisms resistant to antibiotics. The purpose of this study was to map the prevalence of antibiotic-resistant E. coli bacteria in cats and to determine the degree of cat owners' comprehension as a risk factor for the development of antimicrobial resistance. In this investigation, 353 cat anal swab samples were found to contain E. coli. The study was carried out in 2023 between March and May. The Mueller Hilton Agar medium was used to test for multidrug resistance to beta-lactam, aminoglycoside, and tetracycline class antibiotics using the diffusion method. Using a questionnaire, the degree of knowledge on antibiotic resistance among 373 cat owners was assessed. Respondent variables include identification, knowledge, demeanor, attitude, and cat care. After that, data were descriptively examined. E. coli was detected in 87.82% (310/353) of the cat anal swab samples (n = 353) in this investigation. Additionally, multidrug resistance was shown in 7.4% (23/310) of the isolates; this frequency was higher in stray cats (8.75%) than in domestic cats (6%). For ampicillin, tetracycline, and streptomycin, the rates of antimicrobial resistance were 28.39% (88/310), 15.81% (49/310), and 14.84% (46/310), in that order. According to an analysis of the questionnaires used to gauge cat owners' comprehension of antimicrobial-resistant events, 64.3% (240/373) of the owners did not know what antimicrobial resistance was. In addition, 72.7% (271/373) of the cat owners were aware of the medications their cats were given, and 66% (246/373) of them knew how to give antibiotics to their pets. These findings are consistent with the findings of another survey that showed 70% (261/373) of cat owners took their sick cats to the veterinarian. Compared to domestic cats, stray cats in this study had a higher rate of multidrug resistance. This is consistent with the relatively positive findings of a survey on cat owners' comprehension of cat maintenance and care; yet, the poor awareness of antimicrobial resistance among cat owners may contribute to its emergence. To raise awareness regarding antimicrobial resistance in cats, cat owners need to get education.